Understanding socio-ecological drivers of spatial allocation choice in a multi-species artisanal fishery: A Bayesian network modeling approach. (December 2015) - Naranjo-Madrigal, Helven; van Putten, Ingrid; Norman-López, Ana
Abstract: Effective management of artisanal fisheries requires understanding fishers, their behaviors, and the drivers that underpin their choices. Behavioral drivers are critical links in understanding the interactions between social and ecological systems and can help inform effective management approaches. A Bayesian Belief Network modeling approach was used to investigate a diverse range of qualitative and quantitative social and ecological drivers of spatial location choice in a multi-species artisanal dive fishery in Costa Rica. Empirical and observer data used to populate the BBN showed the influence of economic factors, environmental conditions as well as social interactions on the decision-making process of spatial location choice. Good governance scenarios represented by Responsible Fisheries Marine Areas Management were analyzed for both hookah and free diving methods to assess the effects of responsible fishing on the fishers and the fishery. Model based-scenario analysis suggests that management interventions should consider the fisher's potential behavioral responses in the context of environmental variability, dependence on cultural assets, and food security. The results show that there is a need to understand fisher's decisions based on broad socio-ecological system understanding and consider the environmental outcomes alongside food security and the cultural significance of different marine species to fishing communities. Highlights: Environmental and socio-economic factors drive location choice in dive fishery. A Bayesian model can explain spatial location choice in artisanal fishery. Fisher's weigh resource availability and social-cultural factors in decisions. Traditional ecological knowledge, peer pressure and fisher networks matter. Good Governance management is contextual to environmental and socio-cultural aspects.